Association of serum klotho with cognitive function among individuals with nonalcoholic fatty liver disease - Feilong Wu; Jie Pan; Mingtao Chen; Xuye Lai; Yingying Gu; Lei Pei; Lili Yang (Frontiers in Aging Neuroscience)
IntroductionThis study investigated the potential link between serum klotho levels and cognitive function in patients with non-alcoholic fatty liver disease (NAFLD).Materials and MethodsUtilizing NHANES data from 2011 to 2014, the research included 356 eligible participants. NAFLD was identified with the United States Fatty Liver Index (US-FLI), and cognition was measured by various tests including the Animal Fluency Test (AFT), Digit Symbol Substitution Test (DSST), Immediate Recall Test (IRT), and Delayed Recall Test (DRT). Weighted logistic regression and restricted cubic splines were employed to analyze the relationship between klotho levels and cognitive scores.ResultsA significant nonlinear association was observed between klotho levels and the performance in DSST and Delayed Recall Test (DRT). After controlling for confounding factors, the study found a positive association between higher serum klotho levels and improved cognitive performance in both AFT and DSST. However, there was no significant relationship between klotho levels and the IRT or DRT, regardless of whether the natural logarithm or quartile was considered.DiscussionThe findings suggest that a higher serum klotho level may be positively correlated with better cognitive performance in NAFLD patients.